Structural engineering of transmission lines - Catchpole, Peter; Fife, Buck (ICE Publishing, 2014)
'Structural Engineering of Transmission Lines' provides practicing engineers with a comprehensive guide to the structural behaviour of transmission lines and the successful management of transmission line projects. The authors bring together technical knowledge and industry advice to offer extensive practical guidance on the design, construction and management of transmission lines. Taking an international approach, the book details the considerations, methods and outcomes of projects in different parts of the world where the constraints and opportunities of resources, climate and culture are unique.